Beyond Statistics: How can we achieve universal basic education of acceptable quality in Uganda? - Nabwowe, Angella; Mncwabe, Nokukhanya (My University, 2014)
The Right to Education is guaranteed under article 30 of the Constitution of the Republic of Uganda; the country is, moreover party to International Conventions that guarantee this right, including the International Convention on Economic, Social and Cultural Rights (ICESCR), the Convention on the Rights of the Child (CRC), the African Charter on Human and Peoples’ Rights (ACHPR) and the African Charter on the Rights and Welfare of the Child (ACRWC). Uganda has been praised for introducing free Universal Primary Education (UPE), and the scheme has indeed registered some successes over the years – including an increase in school enrolment rates countrywide, with girls and children from poor families benefiting in particular. Notwithstanding these successes, however, basic primary education is not without its challenges, which have the potential to undermine the quality of education offered and to erode the gains attained if remedial action is not prioritized. The deteriorating quality of education has been documented in several studies, such as UWEZO (2014), and the Ministry of Education and Sports, together with the Stromme Foundation, Save the Children, UNICEF, and UNHCR (2014).